The role of mining in Kyrgyzstan's social acceptance of protest - Sternberg, T.; Tchoroev, A.; Toktomushev, K. (Resources Policy, 2023)
Mining-driven conflict is endemic across developing nations, most often centred on local benefit, jobs and environmental impact. Since the 1990s much attention has focused on the concept of Social License to Operate (SLO) to reduce company-community disputes. Building on skills gained from SLO, an intriguing next step is to posit that such processes can spread beyond mining to inform and instigate other forms of protest. Here we explore how extractive experience has influenced infrastructure protest regionally. Investigating Naryn Province in Kyrgyzstan reflects how techniques and experience learned from mining can inform and inspire community action. Research draws on interviews at the Solton Sary mine in 2019 and the planned At-Bashy logistics centre in 2020 to examine if a successful anti-mine manifestation contributed to a broader social acceptance of protest in the region and country. Whilst residents stated that fear of foreign encroachment was paramount, adapted protest methods were effective in cancelling the logistics centre.